The road home - Lewis, Beverly, 1949- (Bethany House, a division of Baker Publishing Group, 2018)
Sent from Michigan to Pennsylvania following the tragic death of her Amish parents, Lena Rose Schwartz grieves her loss and the separation from her nine siblings. Beside the fact that Lena has never been so far from home, she hasn't met the family she will now be living with. But worse than that is having to live apart from her close-knit brothers and sisters. How will they manage without her to care for them--especially six-year-old Chris? And will her new beau, Hans Bontrager, continue to court her despite the many miles between them? Yet even as Lena Rose holds on to hope for a reunion with those she loves most, she discovers that Lancaster holds charms of its own. Is she willing to open her heart to new possibilities?